EXTRACTION, ISOLATION, AND CHARACTERIZATION OF BIOACTIVE COMPOUNDS AND ESSENTIAL OIL FROM SYZYGIUM JAMBOS - Ghareeb, Mosad Ahmed; Hamed, Manal Mortady; Abdel-aleem, Abdel-aleem Hassan; Saad, Amal Mohamed; Abdel-aziz, Mohamed Sayed; Hadad Hadad, Asmaa (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Over the past few decades, phenolic compounds become important due to it has been associated with protection against different diseasesand sensory point of vision. Hence, at the present study, there has been a growing interest to carry out structural elucidation and characterization ofthe pure isolates from Syzygium jambos. Methods: S. jambos dried powder leaves were extracted by soaking in 85% methanol solvent at room temperature 25Â±2Â°C. The antioxidative activityof the isolates was assessed according to 2,2’-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and phosphomolybdenum assays. Results: A total of 8 compounds were isolated from the n-butanol extract of S. jambos (Family Myrtaceae) plant, they were identified as quercetin-3-O-rutinoside (1), prenylbenzoic acid 4-Î²-D-glucoside (2), morolic acid 3-O-caffeate (3), 5,4’-dihydroxy, 7-methoxy, 6-methyl-flavone (4),3,4,5-trihydroxybenzoic acid (5), quercetin (6), isoetin-7-O-Î²-D-glucopyranoside (7), and (4’-hydroxy-3’-methoxyphenol-Î²-D-[6-O-(4â€-hydroxy-3â€,5â€-dimethoxylbenzoate)] glucopyranoside) (8). Compounds 5 and 6 showed the most radical scavengers among the tested compounds with SC50 values of5.50 and 4.30 Î¼g/ml, respectively, compared to ascorbic acid as standard and the total antioxidant capacity (TAC) values of 605.0 and 680.59 mg ascorbicacid equivalent/g compound, respectively. In vitro antimicrobial activities of the isolated compounds were tested using disc agar plate method againstfour pathogenic microbial strains including Gram-positive, Gram-negative bacteria and yeast with inhibition zones from 9 to 19 mm. Gas chromatographymassspectrometry analysis for the essential oil provides twenty four identified components representing 92% of its total oil composition. Conclusion: The results supported that S. jambos could be attributed to sources of natural antioxidant and antimicrobial applications.